O aperfeiçoamento dos assistentes sociais no Programa de Residência Multiprofissional em Saúde de um hospital universitário - Dias, Heloísa Helena Rodrigues (2014)
INTRODUCTION: This study is about knowing the perception of former students and preceptors relative to the Multidisciplinary Residency in Health at the Federal University of Goiás Public Hospital during the period of 2010 to 2012. OBJECTIVES: To analyze the perception of social workers (preceptors and former students) with respect to their performance, as well as understand the deployment and implementation process of the Multidisciplinary Residency in Health Program (PRMS as the portuguese acronym); identify the necessary skills to labor in the SUS and describe the difficulties encountered in the field of action. METHODS: A descriptive and exploratory study with qualitative approach. The instrument was a semi-structured interview with open questions recorded from five preceptors and twelve former social workers students. The transcribed interviews were submitted to content analysis proposed by Bardin and using the software ATLAS TI. The analyzes were performed taking into account the formation and the professional performance in residence and presented the factors that affect the field of action. RESULTS: It’s necessary to: acquire new knowledges to work in multidisciplinary teams; to develop specific competencies for preceptorship and for work in the SUS; to enhance inter-branch, multi-professional and interpersonal relationships. CONCLUSION: The analysis of the content of the interviews showed that the goals of the health multi-professional residence, specifically in Social Work, have been achieved, though, it is necessary to consider specific actions to improve skills that contribute to the exercise of the preceptor role and to work in the SUS focused on interdisciplinarity and integrality of health care.